2016
DOI: 10.1002/jor.23320
|View full text |Cite
|
Sign up to set email alerts
|

Chordoma‐derived cell line U‐CH1‐N recapitulates the biological properties of notochordal nucleus pulposus cells

Abstract: Intervertebral disc degeneration proceeds with age and is one of the major causes of lumbar pain and degenerative lumbar spine diseases. However, studies in the field of intervertebral disc biology have been hampered by the lack of reliable cell lines that can be used for in vitro assays. In this study, we show that a chordoma‐derived cell line U‐CH1‐N cells highly express the nucleus pulposus (NP) marker genes, including T (encodes T brachyury transcription factor), KRT19, and CD24. These observations were fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, our previous study showed that MTNR1B can also interact with Gαi2 in the chordoma cell lines, U-CH1 and MUG-CC1 [54]. We speculate that this coincidence may be related to the homology between NP cells and chordoma cell lines [57].…”
Section: Discussionmentioning
confidence: 70%
“…Interestingly, our previous study showed that MTNR1B can also interact with Gαi2 in the chordoma cell lines, U-CH1 and MUG-CC1 [54]. We speculate that this coincidence may be related to the homology between NP cells and chordoma cell lines [57].…”
Section: Discussionmentioning
confidence: 70%
“…U-CH1-N cells are a chondroma-derived cell line that share certain biological characteristics with notochordal NP cells. 33 Cells were cultured in minimum essential medium alpha (MEM-alpha; Sigma-Aldrich) with 10% FBS and 1% penicillin-streptomycin in a humidified atmosphere containing 5% CO 2 at 37°C. U-CH1-N cells were seeded into six-well plates at a density of 2 × 10 5 cells/well or into 100 mm dishes at a density of 1 × 10 6 cells/dish 1 day before treatment, respectively.…”
Section: U-ch1-n Cell Lines and Culturementioning
confidence: 99%
“…This review follows the consensus review on nucleus pulposus phenotype of the ORS Spine Research Interest Group (now Spine Section) . Improved functional nucleus pulposus cell markers are reported that highlight notochordal markers, clarify their distinction from articular chondrocytes, and include novel molecular phenotypic changes that also occur with ageing and degeneration . Defining markers of annulus fibrosus phenotype remains a young field and important functional cellular behaviours of annulus cells are described …”
Section: Disc Ageing and Cell Biologymentioning
confidence: 99%